Social Networks: The Survival Strategy Of Indonesian Migrant Workers In Hong Kong - Anggaunitakiranantika, Anggaunitakiranantika (KOMUNITAS: International Journal of Indonesian Society and Culture, 2021)
Transnational migration performed by Indonesian women today is a social transformation in labor participation. This phenomenon is also encountered in the lives of women who decide to become Indonesian migrant workers in Hong Kong. This research aims to analyze and identify the self-actualized survival ability of Indonesian migrant workers in Hong Kong. In addition, this research also investigates the social capital practiced by Indonesian migrant workers in Hong Kong. The descriptive qualitative method was employed as the research method by using an interpretive approach. Data collection in this research utilized purposive sampling on nine Indonesian women migrant workers which was conducted in May 2019 and located in Tsim Tsa Shui, Kowloon district, Hong Kong. By applying the concept of social capital from Fukuyama, research results discovered that the existence of migrant workers network is established in the circle of relatives and families, which becomes the formation basis of social capital. Social capital possessed by Indonesian migrant workers is admitted to be composed of three main elements, firstly, trust in the form of social security to support the continuity of existence of women as migrant workers in Hong Kong, specifically when facing problems. The second element is reciprocal, which is based on the economic shortages experienced and the common feeling and experience of being a migrant worker in Hong Kong. The last element is social interaction, which prioritizes practical and economic interactions by choosing the closest district to where they live and using social media to communicate with each other.